CO2 Detection System in Mixed Gas using MQ-135 Sensor - Salamah, Umi; Hidayah, Qonitatul; Kusuma, Damar Yoga (UNIB Press, 2021)
The increase in CO2 gas occurred very significantly due to the use of fossil fuels, industry, forest fires, volcanic eruptions and natural gas resulting in air pollution. The dangers of CO? gas for humans can cause headaches, sweating, blurred vision, tremors, and loss of consciousness after exposure for five to ten minutes. CO2 is a poisonous gas which is physically colorless and odorless. This characteristic causes many humans to be unaware of the existence of this gas, so that it is exposed and endangers health. Therefore we need a CO2 gas detection system. The difficulty that occurs in the detection of CO2 gas is when the gas is mixed with other gases that have similar material properties. In this research, a CO2 gas detection system is designed to detect the gas when it mixes with other gases using the MQ-135 sensor. The system that has been designed and built is then compared with a standard tool, namely the xm-7000 dragger. The test data analyzed using linear regression showed the results in accordance with 2the value of R = 0.9896 with the conversion equation y = 0.0389x-76.086. With these results provide new opportunities in testing CO2 on gas mixtures that are easier and cheaper.